2013
DOI: 10.1039/c3nr01834b
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic behavior and STDP of asymmetric nanoscale memristors in biohybrid systems

Abstract: We fabricate and characterize asymmetric memristors which show a very strong single-sided hysteresis. When biased in one direction there is hysteresis and in the opposite direction there is a lack of hysteresis. We demonstrate that this apparent lack is actually hysteresis on a much faster time-scale. We further demonstrate that this form of asymmetric behavior correlates very well to the asymmetric structure and function of an actual synapse. The asymmetric memristor device presented here is necessary to corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…Many artificial synaptic devices, which are bionic signal‐processing elements, have been explored by using both two‐terminal memristors and three‐terminal transistors . Take a two‐terminal memristor for example, the conductance of several inorganic devices can be incrementally adjusted by modulating the charge or flux through it to perform as an artificial synaptic element . In addition, transistors can provide an effective platform for the construction of artificial synapses since the channel conductivity of a transistor can be modulated by the gate electrode to emulate the synaptic functions .…”
mentioning
confidence: 99%
“…Many artificial synaptic devices, which are bionic signal‐processing elements, have been explored by using both two‐terminal memristors and three‐terminal transistors . Take a two‐terminal memristor for example, the conductance of several inorganic devices can be incrementally adjusted by modulating the charge or flux through it to perform as an artificial synaptic element . In addition, transistors can provide an effective platform for the construction of artificial synapses since the channel conductivity of a transistor can be modulated by the gate electrode to emulate the synaptic functions .…”
mentioning
confidence: 99%
“…These discrepancies and influences in weight which change according to applied learning rules should be investigated further by alternatively extending the model to include STDP learning rules. We have, for example, demonstrated that STDP learning behavior can be realized in a biohybrid synapse built as a memristor [48]. It is feasible to implement the model in neuromorphic hardware as in parallel memristor bridge synapse-based neural networks, as in an evolving spiking neural network with temporal spike learning, or as a model with implemented dendritic delays [4951].…”
Section: Computational Hough Models At the Neuron Levelmentioning
confidence: 99%
“…However, they are considered as very important elements in new types of computational systems. In particular, several works on memristive devices were done for the mimicking of synapse properties [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The activity in this directions are in progress and several important results have been reported.…”
Section: Introductionmentioning
confidence: 98%